2017
DOI: 10.1007/s00394-017-1499-7
|View full text |Cite
|
Sign up to set email alerts
|

A modified response of NAFLD patients with non-significant fibrosis in nutritional counseling according to GCKR rs1260326

Abstract: Our results show that GCKR rs1260326 T-allele is associated with better response of NAFLD patients to nutritional treatment regarding fasting blood glucose, but not oxLDL levels. Despite this important finding in the field of nutrigenetics, it is tricky to generalize this effect unless larger studies are conducted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 28 publications
0
3
0
1
Order By: Relevance
“…Several studies have explored the interaction between GCKR rs1260326 variant and the environmental factors [74,76,77]. In an open-labeled and single-arm clinical trial, Kaliora et al demonstrated that T allele carriers respond better to nutritional intervention in terms of fasting blood glucose levels compared to non-carriers, in 44 overweight adults with NAFLD which have been received dietary counseling for six months [76]. For instance, whole-grain supplementation is associated with lower fasting glucose and insulin concentrations independently of demographics, other dietary and lifestyle factors and BMI [78].…”
Section: Gckr: a Potential Carbohydrates' Modulator To Improve Liver mentioning
confidence: 99%
“…Several studies have explored the interaction between GCKR rs1260326 variant and the environmental factors [74,76,77]. In an open-labeled and single-arm clinical trial, Kaliora et al demonstrated that T allele carriers respond better to nutritional intervention in terms of fasting blood glucose levels compared to non-carriers, in 44 overweight adults with NAFLD which have been received dietary counseling for six months [76]. For instance, whole-grain supplementation is associated with lower fasting glucose and insulin concentrations independently of demographics, other dietary and lifestyle factors and BMI [78].…”
Section: Gckr: a Potential Carbohydrates' Modulator To Improve Liver mentioning
confidence: 99%
“…Of note, we first discovered that rs1260326-C in the GCKR gene was linked to waist circumference in the elderly Chinese Han population with lean NAFLD. This connection may be attributed to the disrupted glucose and lipid metabolism regulated by GCKR 31 , leading to abnormal waist circumference.…”
Section: Discussionmentioning
confidence: 99%
“…Другим же его проявлением является влияние на уровень глюкозы и СРБ (С-реактивный белок) в крови, полиморфизм rs780094 способствует снижению показателей глюкозы, но приводит к повышению провоспалительного маркера СРБ у всех носителей аллеля ТТ вне зависимости от наличия НАЖБП [34,35]. При этом носительство мутантного полиморфизма rs1260326 способствует повышению уровня глюкозы в крови, который, однако, лучше корректируется диетой [36].…”
Section: влияние гена Gckr на развитие неалкогольной жировой болезни ...unclassified